History dissemination in audiovisual languages. A semiotic approach: the case of cinema and television - Tenoch Cid Jurado, Alfredo (InMediaciones de la Comunicación, 2018)
In this article, the main problems related to the dissemination of history in film and television are approached from a semiotic perspective. The behavior of scientific language involves processes, systems and structures, which have been developed in a specifically manner in film and television. The structure of the organization of messages with informative function in the field of history shows behaviors and problems common of the audiovisual communication used in a narrative process. Some of these problems are specialized language, fiction, plausibility, cognitive schemes and explanatory effect. A semiotic approach allows us to reflect on the behavior and its possible future developments in other audiovisual systems; virtual reality, video game and hyperreality.